PENTINGNYA PERANAN GURU BIMBINGAN DAN KONSELING DALAM PERKEMBANGAN KARIR PADA SISWA SEKOLAH DASAR - Yulianti, Yulianti; Anastasya, Lia; Ayunabilla, Ayunabilla; Labibah, Adzra Reva; Febia, Alma Aura; Riski, Aria Dwi (Dharmas Education Journal (DE_Journal), 2024)
This research aims to identify the role of guidance and counseling teachers in helping students develop an understanding of their career choices, as well as analyzing the effectiveness of guidance and counseling programs in facilitating students' career development at the elementary school level. The Narrative Review method is used because of its advantages in compiling summaries of existing knowledge, identifying gaps, and facilitating innovation in scientific research. The research results show the important role of guidance and counseling teachers in shaping students' career understanding in elementary schools, by implementing a holistic approach, using effective media, and adopting innovations in career guidance. The holistic approach emphasizes the importance of considering internal and external factors in forming students' career understanding. Appropriate and effective media, such as guidance boards and information technology, also help students broaden their career horizons. Innovation in career guidance by guidance and counseling teachers, especially to develop Career Awareness in the Industrial Revolution Era 4.0, is the main focus. Techniques such as curriculum infusion, group activities, and community involvement are used to prepare students well to face future career challenges. By implementing a holistic approach, using media wisely, and continuing to innovate in career guidance methods, elementary school students are expected to have optimal readiness to compete in the future.